Chiral Lanthanide Complexes with l- and d-Alanine: An X-ray and Vibrational Circular Dichroism Study - Lyczko, Krzysztof (Molecules, 2020)
A whole series of [Ln(H(2)O)(4)(Ala)(2)](2)(6+) dimeric cationic lanthanide complexes with both l- and d-alanine enantiomers was synthesized. The single-crystal X-ray diffraction at 100 and 292 K shows the formation of two types of dimers (I and II) in crystals. Between the dimer centers, the alanine molecules behave as bridging (μ(2)-O,O’-) and chelating bridging (μ(2)-O,O,O’-) ligands. The first type of bridge is present in dimers I, while both bridge forms can be observed in dimers II. The IR and vibrational circular dichroism (VCD) spectra of all l- and d-alanine complexes were registered in the 1750–1250 cm(−1) range as KBr pellets. Despite all the studied complexes are exhibiting similar crystal structures, the spectra reveal correlations or trends with the Ln–O1 distances which exemplify the lanthanide contraction effect in the IR spectra. This is especially true for the positions and intensities of some IR bands. Unexpectedly, the ν(C=O) VCD bands are quite intense and their composed shapes reveal the inequivalence of the C=O vibrators in the unit cell which vary with the lanthanide. Unlike in the IR spectra, the ν(C=O) VCD band positions are only weakly correlated with the change of Ln and the VCD intensities at most show some trends. Nevertheless, this is the first observation of the lanthanide contraction effect in the VCD spectra. Generally, for the heavier lanthanides (Ln: Dy–Lu), the VCD band maxima are very close to each other and the mirror reflection of the band of two enantiomers is usually better than that of the lighter Lns. DFT calculations show that the higher the multiplicity the higher the stability of the system. Actually, the molecular geometry in crystals (at 100 K) is well predicted based on the highest-spin structures. Also, the simulated IR and VCD spectra strongly depend on the Ln electron configuration but the best overall agreement was reached for the Lu complex, which is the only system with a fully filled f-shell.